Fatty Acid Composition of Cocoa Beans from Yogyakarta Special Region for the Establishment of Geographical Origin Discriminations - Retno Utami Hatmi; Makhmudun Ainuri; Anggoro Cahyo Sukartiko (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2021)
The composition of fatty acids in cocoa beans, which affect the characteristics of the processed products, is dependent on the geographic location. This research aimed to identify the fatty acid composition of cocoa beans from the Special Region of Yogyakarta (Patuk Gunungkidul and Kalibawang Kulon Progo), used as a geographical origin discrimination parameter. The data were analyzed using ANOVA and Partial Least Square – Discriminant Analysis (PLS-DA). The results showed that the composition from Patuk Gunungkidul and Kalibawang Kulon Progo were dominated by stearic (35.23%), oleic (33.12%), and palmitate acids (27%). The developed method combined with PLS-DA was successfully employed the fatty acid composition to discriminate the geographic origin of cocoa beans in the Special Region of Yogyakarta.